2002
DOI: 10.1002/jrs.890
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent Raman study of L‐arginine hydrochloride monohydrate single crystal

Abstract: Polarized Raman spectra of L-arginine hydrochloride monohydrate single crystal were studied at temperatures ranging from 295 to 10 K. The behavior of the linewidth, wavenumber and intensity of several bands is discussed and related to some particular vibrational modes associated with hydrogen bonds or even to other vibrations, such as CN, CCC, CCN and CH vibrations. The disappearance of some bands in the lattice vibrational region was associated with a phase transition undergone by the crystal between 100 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…IR spectroscopic data are assigned and compared with known ones ofsimple amino acids and arginine-and alaninecontaining peptides. 26 A multiple band in the 850-550 cm (Table II) in the same dichroic ratio indicated a colinearity of their transition moments, which is in agreement with the theoretical structure [ Figure 3(3)] as well. However, the last procedure provoked an elimina-FIGURE 3 Nonpolarized IR (1) and reduced IR-LD spectra of GGArg after elimination of 3288 cm -1 (2) and 3080 cm -1 (3) peaks.…”
Section: Ir Spectroscopic Datasupporting
confidence: 85%
“…IR spectroscopic data are assigned and compared with known ones ofsimple amino acids and arginine-and alaninecontaining peptides. 26 A multiple band in the 850-550 cm (Table II) in the same dichroic ratio indicated a colinearity of their transition moments, which is in agreement with the theoretical structure [ Figure 3(3)] as well. However, the last procedure provoked an elimina-FIGURE 3 Nonpolarized IR (1) and reduced IR-LD spectra of GGArg after elimination of 3288 cm -1 (2) and 3080 cm -1 (3) peaks.…”
Section: Ir Spectroscopic Datasupporting
confidence: 85%
“…Related to the first point we remember that Raman spectroscopy study have suggested the occurrence of a phase transition undergone by LAHW crystal at about 110 K [8]. This phase transition was inferred mainly by the change of band profiles in the low-wavenumber region of the spectra.…”
Section: Figmentioning
confidence: 87%
“…It was observed that under high temperature conditions LAHW begins to lost water of crystallization at 70 o C and at 200 o C about two-third of it are eliminated [7]. Under low temperature conditions, on the other hand, it was observed through Raman scattering technique, evidence of a phase transition undergone by LAHW between 100 and 110 K [8]. Although in the paper of Ref.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The vibrational spectra of systems with hydrogen bonds are important sources of information on the dynamics and nature of the interaction. 12 Hammer et al 36 studied the single-crystal IR spectroscopy of very strong hydrogen bonds in pectolite and serandite. Foglizzo and Novak 37 reported the low-wavenumber infrared and Raman spectra of hydrogen-bonded pyridinium halides.…”
Section: Other Vibrationsmentioning
confidence: 99%